1993
DOI: 10.1083/jcb.121.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor/c-erbA: control of commitment and differentiation in the neuronal/chromaffin progenitor line PC12.

Abstract: Abstract. The c-erbA proto-oncogenes encode nuclear receptors for thyroid hormone (T3), a hormone intimately involved in mammalian brain maturation. To study thyroid hormone receptor (TR) action on neuronal cells in vitro, we expressed the chicken c-erbA/ TRot-1 as well as its oncogenic variant v-erbA in the adrenal medulla progenitor cell line PC12. In the absence of T3, exogenous TRc~-I inhibits NGF-induced neuronal differentiation and represses neuron-specific gene expression. In contrast, TRo~-I allows nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 88 publications
4
36
0
Order By: Relevance
“…In line with the inability of the v-ErbA protein to bind T 3 , addition of hormone cannot release the repression of the NGF-induced neuronal differentiation. Besides this, T 3 does not affect the viability of PC12+v-erbA cells (80).…”
Section: Effects Of Trs In Neuronal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the inability of the v-ErbA protein to bind T 3 , addition of hormone cannot release the repression of the NGF-induced neuronal differentiation. Besides this, T 3 does not affect the viability of PC12+v-erbA cells (80).…”
Section: Effects Of Trs In Neuronal Cellsmentioning
confidence: 99%
“…PC12 cells expressing the chicken TR-a gene (PC12+TRa-1) from an integrated Moloney murine leukemia-based retrovirus showed a very interesting phenotype: they were able to respond to the initial steps of the neuronal differentiation triggered by NGF with expression of a series of immediate early genes (c-jun, junB, junD, c-fos, fra-1, NGFI-A, NGFI-B) and formation of short processes (spikes), but were, however, blocked in later phases of differentiation with no elongation of neurites and the inhibition of the expression of the NGFinduced neuronal genes (transin, SCG10, neurofilament-68, NCAM, GAP43) (80). Thus, in the absence of hormone TR expression causes an inhibition of the NGFinduced neuronal differentiation pathway.…”
Section: Effects Of Trs In Neuronal Cellsmentioning
confidence: 99%
“…However, to what extent C-to-S mutant PTPs can indeed be relied on to be specific and true dominant-negatives is as yet still unclear; hence, interpretation of the significance of this observation is probably premature. Assessment of mRNA levels by Northern blotting for the metalloprotease transin, a late marker for NGF-induced neuronal differentiation of PC12 cells (39,40), revealed that the EGF-induced neurite extension correlated fully with expression of this marker. EGF treatment lead to transin induction in cells expressing wt RPTP␣ or RPTP␣Y798F but not RPTP␣CCSS; moreover, this effect was stronger in RPTP␣Y798F than in wt RPTP␣-expressing cells (supplemental data included in the on-line version of manuscript).…”
Section: Rptp␣ Stimulates Egf-induced Neurite Outgrowth In a Mannermentioning
confidence: 99%
“…These brain regions (hippocampus, basal forebrain) have particularly high levels of thyroid hormone receptors during development and are sites where thyroid hormones regulate nerve growth factor (NGF) production (34)(35)(36). Thyroid hormones and NGF cooperate in the development of specific cholinergic systems in the central nervous system (37), and thyroid hormones could regulate neurotransmitter development through their action on NGF production in these specific regions. Hypothyroidism decreases choline acetyltransferase (ChAT) quantities in brain regions innervated by these neurons (32) because thyroid hormones serve as positive regulatory factors for the ChAT gene (38).…”
Section: Synaptogenesis and Myelinogenesismentioning
confidence: 99%